2000
DOI: 10.1093/jexbot/51.350.1555
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Arabidopsis thaliana seedlings under water deficit studied by control of water potential in nutrient‐agar media

Abstract: We have characterized the growth responses of Arabidopsis thaliana seedlings to water deficit. To manipulate the water potential, we developed a method whereby the nutrient-agar medium could be supplemented with polyethylene glycol (PEG 8000); PEG was introduced into gelled media by diffusion, which produced media with water potential as low as -1.6 MPa. For dark-grown plants, hypocotyl growth had a hyperbolic dependence on water potential, and was virtually stopped by -1 MPa. In contrast, primary root elongat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
180
1
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(206 citation statements)
references
References 35 publications
16
180
1
2
Order By: Relevance
“…However, the effects of WD on LR initiation have been poorly studied in general [13]. A reduction in LR number has been reported for Arabidopsis subjected to osmotic stress (polyethylene glycol), but only emerged and visually detectable LRs were taken into account, which made it unclear at what stage LR formation was (partially) disrupted [26]. Further experiments revealed that osmotic stress blocks LR formation at the emergence stage in Arabidopsis [27].…”
Section: Discussion (A) a Novel System For Monitoring Early Events Ofmentioning
confidence: 99%
“…However, the effects of WD on LR initiation have been poorly studied in general [13]. A reduction in LR number has been reported for Arabidopsis subjected to osmotic stress (polyethylene glycol), but only emerged and visually detectable LRs were taken into account, which made it unclear at what stage LR formation was (partially) disrupted [26]. Further experiments revealed that osmotic stress blocks LR formation at the emergence stage in Arabidopsis [27].…”
Section: Discussion (A) a Novel System For Monitoring Early Events Ofmentioning
confidence: 99%
“…Plant roots are responsible for water uptake and are the first plant organ to encounter soil water deficiency. Accordingly, roots exhibit great architectural plasticity to help the plants to better adapt to water availability [1][2][3]. Under normal conditions lateral roots proliferate; under drought stress, both the initiation and the elongation of lateral roots are reduced [1][2][3], presumably facilitating primary root elongation for water uptake from deeper soil.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, roots exhibit great architectural plasticity to help the plants to better adapt to water availability [1][2][3]. Under normal conditions lateral roots proliferate; under drought stress, both the initiation and the elongation of lateral roots are reduced [1][2][3], presumably facilitating primary root elongation for water uptake from deeper soil. Whereas the phytohormone auxin plays an essential role in promoting lateral root initiation and elongation [4,5], the stress hormone abscisic acid (ABA) inhibits lateral root generation [3,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…For example, this occurs in nodal (adventitious) roots of maize, which must penetrate through the often dry surface soil (Westgate & Boyer 1985), and in primary roots of a range of species, which helps seedling establishment under dry conditions by ensuring a supply of water before shoot emergence (Sharp, Silk & Hsiao 1988;Spollen et al . 1993;van der Weele et al . 2000).…”
Section: Introductionmentioning
confidence: 99%